Chemical Properties of Vitis Vinifera Carménère Pomace Extracts Obtained by Hot Pressurized Liquid Extraction, and Their Inhibitory Effect on Type 2 Diabetes Mellitus Related Enzymes - Nils Leander Huamán-Castilla; David Campos; Diego García-Ríos; Javier Parada; Maximiliano Martínez-Cifuentes; María Salomé Mariotti-Celis; José Ricardo Pérez-Correa (MDPI AG, 2021)
Grape pomace polyphenols inhibit Type 2 Diabetes Mellitus (T2DM)-related enzymes, reinforcing their sustainable recovery to be used as an alternative to the synthetic drug acarbose. Protic co-solvents (ethanol 15% and glycerol 15%) were evaluated in the hot pressurized liquid extraction (HPLE) of Carménère pomace at 90, 120, and 150 °C in order to obtain extracts rich in monomers and oligomers of procyanidins with high antioxidant capacities and inhibitory effects on α-amylase and α-glucosidase. The higher the HPLE temperature (from 90 °C to 150 °C) the higher the total polyphenol content (~79%, ~83%, and ~143% for water-ethanol, water-glycerol and pure water, respectively) and antioxidant capacity of the extracts (Oxygen Radical Absorbance Capacity, ORAC), increased by ~26%, 27% and 13%, while the half maximal inhibitory concentration (IC50) decreased by ~65%, 67%, and 59% for water-ethanol, water-glycerol, and pure water extracts, respectively). Water-glycerol HPLE at 150 and 120 °C recovered the highest amounts of monomers (99, 421, and 112 µg/g dw of phenolic acids, flavanols, and flavonols, respectively) and dimers of procyanidins (65 and 87 µg/g dw of B1 and B2, respectively). At 90 °C, the water-ethanol mixture extracted the highest amounts of procyanidin trimers (13 and 49 µg/g dw of C1 and B2, respectively) and procyanidin tetramers of B2 di-O-gallate (13 µg/g dw). Among the Carménère pomace extracts analyzed in this study, 1000 µg/mL of the water-ethanol extract obtained, at 90 °C, reduced differentially the α-amylase (56%) and α-glucosidase (98%) activities. At the same concentration, acarbose inhibited 56% of α-amylase and 73% of α-glucosidase activities; thus, our grape HPLE extracts can be considered a good inhibitor compared to the synthetic drug.